Analisis Efektivitas Program Pendidikan dan Pelatihan dalam Meningkatkan Kinerja Pegawai Rekam Medis - Muhammad Irfan Bashori; Nur Cahyadi (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
There is an era 4.0 where information and communication technology is maximally utilized. Medical records and registration are written evidence of the service process that contains the patient’s clinical data during the diagnosis and treatment process. Medical record management in hospitals is to support the achievement of orderly administration in order to achieve hospital goals, namely improving the quality of health services in hospitals by conducting education and training programs for employees. The purpose of this study is to measure the extent to which the success of the program, the success of the program objectives, satisfaction with the program, the level of input and output produced and the achievement of overall goals need attention from the organizers of education and training (diklat). This research is a qualitative research using primary data and secondary data. Data collection techniques in this study were through observation and interviews. The selection of informants in this study was carried out using purposive sampling method. The results of this study as what has been conveyed by the three informants can be said that the implementation of the education and training program (diklat) in xyz hospital has not been able to meet its objectives, namely to increase employee motivation, employee productivity, and organizational performance.